A MINORITY BOOKS: SOME ISSUES CONCERNING THE CIRCULATION OF CULTURAL GOODS - Legendre, Bertrand (Knygotyra, 2016)
The position of foreign literature in France is highly related to the positions of the countries and languages these texts are coming from. Clearly dominated by the Anglo-Saxon culture, the French market has been opened to the Scandinavian literature and to the South-American one. African literatures remain one of the poor parts of the foreign literature in the French publishers’ lists. Human sciences don’t stay away from the dominating systems’ rules and the mood (or the need) of best-sellers. This paper strives to analyse the evolution of this situation. If we could consider that the mainstream logics will continue to dominate the publishing activity, we would choose to focus, from a socio-economic point of view, on some practices and conditions potentially able to modify the circulation of texts. Our hypothesis consists in thinking it is useless to wait that the economic system of publishing industry make place for minority books. As a consequence, the question is to look for new ways of the international circulation of intellectual goods.
Keywords: foreign literature; African literatures; cultural diversity; concentration; independence; self-publishing